Diagnosis and Treatment of Neonatal Seizures - A Review: Diagnosis and Treatment of Neonatal Seizures - A Review - Hesaraki, Mehran (International Journal of Pharmaceutical & Biological Archive, 2018)
Over the past few decades, the prognosis of neonatal seizures has experienced considerable enhancement due to the improvement in neonatal and infant care. The mortality rate of neonatal seizures has fallen from 40% to 20%, and the relationship between electro encephalogram (EEG) and prognosis has become quite clear. The underlying cause of seizures is a major determinant of the outcome of the disease. For example, patients with secondary seizures and hypoxic-ischemic encephalopathy have only 50% chance of normal development and total recovery, while newborns with secondary seizures and subarachnoid hemorrhage or better hypocalcemia have higher chances of recovery. Searches were conducted by two independent researchers in international (PubMed, Web of Science, Scopus, and Google Scholar) and national (SID and Magiran) databases for related studies from the inception of the databases to September 2017 (without time limitation) in English and Persian languages. It is possible to achieve accurate diagnosis through checking the history before birth and performing a thorough physical examination in some rare cases. Depending on the case, tests or additional actions can be done. EEG is the primary means for diagnosis and may exhibit paroxysmal activity in the difference between seizures or may produce electrographic seizures in cases where seizure is hidden or latent. One of the most important points in the treatment of neonatal seizures is the diagnosis of underlying cause (such as hypoglycemia, meningitis, drug deprivation, and trauma) because such diagnosis facilitates different approaches to control neonatal seizures. Most experts agree to control all clinical and electrographic seizures. Some others focus merely on clinical seizures. Most centers prefer the first approach. An important point before starting an anticonvulsant drug is to decide if the patient needs intravenous and luteinizing treatment with an initial bolus dose, or it can be easy to start treatment with a prescription for a long-acting medication based on the severity of seizure, duration, and frequency.